2013
DOI: 10.1016/j.bmcl.2013.02.098
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of the receptor binding residues of kisspeptins by positional scanning using peptide photoaffinity probes

Abstract: Kisspeptins, endogenous peptide ligands for GPR54, play an important role in GnRH secretion. Since in vivo administration of kisspeptins induces increased plasma LH levels, GPR54 agonists hold promise as therapeutic agents for the treatment of hormonal secretion diseases. To facilitate the design of novel potent GPR54 ligands, residues in kisspeptins that involve in the interaction with GPR54 were investigated by kisspeptin-based photoaffinity probes. Herein, we report the design and synthesis of novel kisspep… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
8
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
5
1

Relationship

2
4

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 36 publications
0
8
0
Order By: Relevance
“…For the Kp-14-based probe 4, a polyethylene glycol (PEG) linker was employed between the fluorophore and the peptide N-terminus to avoid the possibility of reduced binding affinity resulting from the bulky fluorophore group. 23 Several TMR-labeled kisspeptin derivatives were synthesized. The peptide chains for Kp-52 and Kp-14 were constructed using Fmoc-based solid phase peptide synthesis (SPPS) on CLEAR-Amide resin and NovaSyn TGR resin, respectively (Scheme 1).…”
Section: Design and Synthesis Of Kisspeptin-based Fluorescent Probes mentioning
confidence: 99%
See 1 more Smart Citation
“…For the Kp-14-based probe 4, a polyethylene glycol (PEG) linker was employed between the fluorophore and the peptide N-terminus to avoid the possibility of reduced binding affinity resulting from the bulky fluorophore group. 23 Several TMR-labeled kisspeptin derivatives were synthesized. The peptide chains for Kp-52 and Kp-14 were constructed using Fmoc-based solid phase peptide synthesis (SPPS) on CLEAR-Amide resin and NovaSyn TGR resin, respectively (Scheme 1).…”
Section: Design and Synthesis Of Kisspeptin-based Fluorescent Probes mentioning
confidence: 99%
“…We recently developed kisspeptin-based photoaffinity probes, where a photoreactive functional group was conjugated to potentially interactive residues in the sequence. 23 In this particular study, we used a panel of different probes to successfully identify several receptor binding residues for GPR54.…”
Section: Introductionmentioning
confidence: 99%
“…NMR studies using DPC micelles have shown that the C-terminal end of Kp1(10) forms a hydrophobic cluster consisting of Phe6 and Phe10 and the aliphatic chain of Leu8, which probably interacts with the carbon chains of the inner membrane phospholipids (Lee et al 2009a). The N-terminal region may also interact with the receptor as kisspeptin photoaffinity probe experiments with Kp1(54) and Kp1(14) show that the three N-terminal residues (Tyr, Asn, and Trp) can constitute a secondary binding site with KissR1 (Misu et al 2013).…”
Section: Interaction and Evolution Of Kiss/kissr Pairsmentioning
confidence: 99%
“…However, each new unnatural amino acid that is addressed requires relatively large efforts of engineering of the critical RNA and protein components. In contrast, the cysteine/maleimide strategy used in this work has potential to be directly compatible with any new photoreactive probe produced as a maleimide derivative …”
Section: Discussionmentioning
confidence: 99%